Constitutivism about epistemic normativity - Cowie, C; Greenberg, A (Palgrave Macmillan, 2018)
According to constitutivists about epistemic normativity, epistemic normativity is explained by the nature of belief. Specifically, it is explained by the fact that, as a matter of conceptual necessity, belief stands in a normative relation to truth. We ask whether there are persuasive arguments for the claim that belief stands in such a relation to truth. We examine and critique two arguments for this claim. The first is based on the transparency of belief. The second is based on Moore-paradoxical sentences. We develop a common objection to both. Both arguments are reliant on implausible claims about the relation between accepting a norm and being motivated by it. This point has sometimes been made in connection with the transparency of belief. But its development and application to Moore-paradoxical sentences are, we believe, novel.